2015
DOI: 10.1038/ijo.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

What does weight stigma smell like? Cross-modal influence of visual weight cues on olfaction

Abstract: In a variety of personal and professional domains, heavy individuals face stigma associated with their body size. Here we investigate a new method for subtle detection of the negative perceptions consistent with that stigma. In two studies, participants were asked to view images of heavy and thin individuals while smelling substances that, unbeknownst to them, were odorless. Across both studies, the results showed that the substances were perceived to smell worse when they were paired with images of heavy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…That said, it should be stressed that the crossmodal effects of vision on olfaction were pretty small in magnitude in this case. Elsewhere, Incollingo Rodriguez et al ( 2015 ) reported on a couple of studies in which their participants viewed images of heavy (i.e., overweight/obese) and normal weight individuals while smelling coloured substances that, unbeknownst to them, were actually odourless. Across the two studies, the olfactory stimuli were rated as smelling worse when they were paired with images of heavy individuals than when they were paired with images of thin individuals.…”
Section: The Influence Of Odour On Person Perceptionmentioning
confidence: 99%
“…That said, it should be stressed that the crossmodal effects of vision on olfaction were pretty small in magnitude in this case. Elsewhere, Incollingo Rodriguez et al ( 2015 ) reported on a couple of studies in which their participants viewed images of heavy (i.e., overweight/obese) and normal weight individuals while smelling coloured substances that, unbeknownst to them, were actually odourless. Across the two studies, the olfactory stimuli were rated as smelling worse when they were paired with images of heavy individuals than when they were paired with images of thin individuals.…”
Section: The Influence Of Odour On Person Perceptionmentioning
confidence: 99%